2014
DOI: 10.2147/copd.s61347
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine profiling and enrichment analysis reveal the involvement of immunological and inflammatory pathways in stable patients with chronic obstructive pulmonary disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a major global health problem. It results from chronic inflammation and causes irreversible airway damage. Levels of different serum cytokines could be surrogate biomarkers for inflammation and lung function in COPD. We aimed to determine the serum levels of different biomarkers in COPD patients, the association between cytokine levels and various prognostic parameters, and the key pathways/networks involved in stable COPD. In this study, serum levels of 48 cytok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 46 publications
1
14
2
Order By: Relevance
“…Clearly, the lack of a substantial impact of long-term smoking on extracellular IL-16 protein in the blood, as demonstrated in our current study, is in contrast to the corresponding impact on IL-16 protein locally in the airways. 18 20 This is also in contrast to a report from Bade et al 43 who showed an increase in serum IL-16 among COPD subjects (current smokers and ex-smokers) compared with nonsmokers and AS. 43 In our study, the COPD group had a decreased gas diffusion capacity, indirectly suggesting emphysema, whereas the AS group, had a normal gas diffusion capacity, arguing against emphysema.…”
Section: Discussioncontrasting
confidence: 93%
“…Clearly, the lack of a substantial impact of long-term smoking on extracellular IL-16 protein in the blood, as demonstrated in our current study, is in contrast to the corresponding impact on IL-16 protein locally in the airways. 18 20 This is also in contrast to a report from Bade et al 43 who showed an increase in serum IL-16 among COPD subjects (current smokers and ex-smokers) compared with nonsmokers and AS. 43 In our study, the COPD group had a decreased gas diffusion capacity, indirectly suggesting emphysema, whereas the AS group, had a normal gas diffusion capacity, arguing against emphysema.…”
Section: Discussioncontrasting
confidence: 93%
“…However, the expression of inflammatory factors in emphysematous patients with COPD was slightly higher than that in emphysematous smokers. This result is consistent with the view that smokers with high inflammatory levels are more likely to develop COPD 26 . NE, MMP-9 and MMP-12 are important protease family members, and AAT, SLPI and TIMP-1 plays an important role as an anti-protease 9,27,28 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that the expression of IL-6, IL-10, IL-1β, and TNF-α did not significantly differ between both groups, indicative of comparable inflammatory response. The expression of IL-6 was lower than that of other inflammatory factors, which confirmed that the levels of inflammatory factors in lung tissue are different 26 . However, the expression of inflammatory factors in emphysematous patients with COPD was slightly higher than that in emphysematous smokers.…”
Section: Discussionmentioning
confidence: 56%
“…[ 2 67 68 69 ] Increased production of such cytokines, indeed, has been demonstrated, and some of them are considered as therapeutic targets of COPD. [ 69 70 71 ] Moreover, systemic inflammation reflected by elevated C-reactive protein (CRP) in the general population has been linked to osteoporosis and to an increased bone resorption. [ 72 73 74 75 76 77 ] Consistent with a role of inflammation in COPD-associated osteoporosis, COPD patients with lower BMD have been shown to have higher levels of CRP and inflammatory cytokines such as TNF-α, IL-1, and IL-6.…”
Section: Disease-specific Risk Factors For Osteoporosis In Copdmentioning
confidence: 99%